Potential effectiveness of digital therapeutics specialized in executive functions as adjunctive treatment for clinical symptoms of attention-deficit/hyperactivity disorder: a feasibility study - Sun, Tai Hui; Yeom, Ji Won; Choi, Kwang-Yeon; Kim, Jeong-Lan; Lee, Heon-Jeong; Kim, Hyun-Jin; Cho, Chul-Hyun (Frontiers in Psychiatry, 2023)
The role of digital therapeutics (DTx) in the effective management of attention deficit/hyperactivity disorder (ADHD) is beginning to gain clinical attention. Therefore, it is essential to verify their potential efficacy. We aimed to investigate the improvement in the clinical symptoms of ADHD by using DTx AimDT01 (NUROW) (AIMMED Co., Ltd., Seoul, Korea) specialized in executive functions. NUROW, which consists of Go/No-go Task- and N-Back/Updating-based training modules and a personalized adaptive algorithm system that adjusts the difficulty level according to the user’s performance, was implemented on 30 Korean children with ADHD aged 6 to 12 years. The children were instructed to use the DTx for 15 min daily for 4 weeks. The Comprehensive attention test (CAT) and Childhood Behavior Checklist (CBCL) were used to assess the children at baseline and endpoint. In contrast, the ADHD-Rating Scale (ARS) and PsyToolkit were used weekly and followed up at 1 month, for any sustained effect. Repeated measures ANOVA was used to identify differences between the participants during visits, while t-tests and Wilcoxon signed-rank tests were used to identify changes before and after the DTx. We included 27 participants with ADHD in this analysis. The ARS inattention (F=4.080, p=0.010), hyperactivity (F=5.998. p<0.001), and sum (F=5.902, p<0.001) significantly improved. After applying NUROW, internalized (t=-3.557, p=0.001, 95% CI=-3.682–-0.985), other (Z=-3.434, p=0.001, effect size=-0.661), and sum scores (t=-3.081, p=0.005, 95% CI=-10.126–-2.022) were significantly changed in the CBCL. The overall effect was confirmed in the ARS sustained effect analysis even after 1 month of discontinuing the DTx intervention. According to caregivers, the findings indicate that DTx holds potential effect as an adjunctive treatment in children with ADHD, especially in subjective clinical symptoms. Future studies will require detailed development and application targeting specific clinical domains using DTx with sufficient sample sizes.